Radially Phased-Locked Hermite–Gaussian Correlated Beam Array and Its Properties in Oceanic Turbulence - Peiying Zhu; Guiqiu Wang; Yan Yin; Haiyang Zhong; Yaochuan Wang; Dajun Liu (Photonics, 2023)
The descriptions of a radially phased-locked Hermite–Gaussian correlated beam array are introduced, the equation of this beam array in oceanic turbulence is derived, and the intensity profiles of this beam array are shown and analyzed. The results imply that the evolutions of the sub-beam of this beam array in free space are the same as the Hermite–Gaussian correlated beam, while the intensity of this beam array can be adjusted by controlling the initial beam radius <semantics>R</semantics> and the coherence length. The intensity profiles of this beam array in free space have multiple spots during propagation, while the same beam array in oceanic turbulence can become a beam spot due to the influences of <semantics>R</semantics> and oceanic turbulence. The beam array with smaller coherence length in oceanic turbulence retains the splitting properties better during propagation.